Tradition and postmodernity: new challenges for the management of heritage - Herrero Pérez, Nieves (Revista de Antropología Social, 2011)
This paper examines some recent contributions to the analysis of posmodernity and highlights their relevance for the study of cultural heritage using the contemporary jacobean pilgrimage as example. In line with anthropologists that work in the field of cultural heritage in Galicia, the author makes some proposals to counteract the reductive effects of the postmodern regime of signification on cultural production.
Keywords: heritage; postmodernity; jacobean pilgrimage; tourism